Online supervision at the university - A comparative study of supervision on student assignments face-to-face and online - Søren Smedegaard Bengtsen; Gry Sandholm Jensen (Læring og Medier, 2015)
Through an empirical study of supervision on student assignments at the university across face-to-face and online settings, we show firstly the limiting implications of traditional dichotomies between face-to-face and online supervision. Secondly we show that more attention must be given to the way different digital tools influence the supervisory dialogue. These findings illustrate a form of ‘torn pedagogy’; that online tools and platforms destabilize and tear traditional understandings of supervision pedagogy apart. Also we forge a new concept of “format supervision” that enables supervisors to understand and reflect their supervision practice as a deliberate choice between face-to-face and online formats.